INNOVATIVE APPROACHES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Xolmo‘minova Mavluda Rustam qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Innovative  approaches  in  teaching  English  as  a  foreign  language  have transformed  the  traditional  classroom  into  a  dynamic  and  interactive  learning environment. This article explores modern methods, including gamification, flipped classroom, blended learning, and the use of artificial intelligence tools. The practical applications of these approaches are analyzed, highlighting their impact on students’ motivation,  engagement,  and  language  acquisition.  By  integrating  innovative strategies,  teachers  can  enhance  students’  communicative  competence  and  critical thinking skills while fostering a more enjoyable and effective learning experience.